EMR is not inferior to ESD for early Barrett’s and EGJ neoplasia: An extensive review on outcome, recurrence and complication rates - Komeda, Yoriaki; Bruno, Marco; Koch, Arjun (Endoscopy International Open, 2014)
Background and study aims In recent years, it has been reported that early Barrett’s and esophagogastric junction (EGJ) neoplasia can be effectively and safely treated using endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD). Multiband mucosectomy (MBM) appears to be the safest EMR method. The aim of this systematic review is to assess the safety and efficacy of MBM compared with ESD for the treatment of early neoplasia in Barrett’s or at the EGJ.Methods A literature review of studies published up to May 2013 on EMR and ESD for early Barrett’s esophagus (BE) neoplasia and adenocarcinoma at the EGJ was performed through MEDLINE, EMBASE and the Cochrane Library. Results on outcome parameters such as number of curative resections, complications and procedure times are compared and reported.Results A total of 16 studies met the inclusion criteria for analysis in this study. There were no significant differences in recurrence rates when comparing EMR (10/380, 2.6 %) to ESD (1/333, 0.7 %) (OR 8.55; 95 %CI, 0.91 – 80.0, P = 0.06). All recurrences after EMR were treated with additional endoscopic resection. The risks of delayed bleeding, perforation and stricture rates in both groups were similar. The procedure was considerably less time-consuming in the EMR group (mean time 36.7 min, 95 %CI, 34.5 – 38.9) than in the ESD group (mean time 83.3 min, 95 %CI, 57.4 – 109.2).Conclusions The MBM technique for EMR is as effective as ESD when comparing outcomes related to recurrence and complication rates for the treatment of early Barrett’s or EGJ neoplasia. The MBM technique is considerably less time-consuming.